Posteromedial Corner Injury in Knee Dislocations - Stannard, James P.; Black, Brandee S.; Azbell, Chris; Volgas, David A. (The Journal of Knee Surgery, 2012)
Surgeons are often faced with very limited data available to make informed decisions regarding the appropriate treatment of patients with posteromedial corner (PMC) injuries of the knee. This study compared the outcomes of surgical repair versus reconstruction in knee dislocation patients who have sustained injury to the PMC of the knee. Senior author treated 113 consecutive knee dislocations with 115 PMC injuries over 7 years. A total of 71 knee dislocation patients with 73 PMC tears qualified for the study and were followed for a mean of 43 months. Patients who had a PMC repair were assigned to treatment Group A. Group B included patients who had autograft reconstruction of the PMC. Patients who had an allograft PMC were assigned to Group C. A total of 25 patients had a repair, with 5 failures (20%), whereas 48 patients had reconstruction of the PMC with 2 failures (4%). There was a significant difference between the failure rate of PMC repairs and PMC reconstructions. Reconstruction of the PMC using a technique that reestablishes the critical triangle of the medial collateral ligament, the posterior oblique ligament, and the semitendinosus yielded better stability than repair in patients with a knee dislocation that included PMC instability.
Keywords: knee dislocation; posteromedial corner repair; posteromedial corner reconstruction